Development of Static Fluid Multimedia Based on Comics Adobe Photoshop and Comic Life Deluxe - Mayasari, Husna; Sunliensyar, Hafiful Hadi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2016)
Physics textbooks used in learning present more descriptions than pictures, making them less attractive to students. This disinterest causes students to be less interested in reading physics books. Using comics as a learning medium is an alternative to attract students' interest in reading physics books. However, from the field and literature studies conducted, only a very few comics contain learning materials, especially physics materials. This type of research is research and development research using the Borg and Gall model which has been modified according to needs in the field. For this reason, physics comics need to be redeveloped with more colorful pictures, dialogue that is easier to understand and more in-depth material. The results of the perception questionnaire analysis conducted on 24 students of class and the percentage of aspects of using comics in student learning activities is 86% (very good).